Angular reconstruction of a lead scintillating-fiber sandwiched electromagnetic calorimeter - 李祖豪 许伟伟 王玲玉 张诚 唐志成 严琪 杨民 吕雨生 陈国明 陈和生 (Chinese physics C, 2014)
The Neighbor Cell Deposited Energy Ratio （NCDER） is a new method that is proposed to reconstruct incidence position in a single layer for a 3-dimensional imaging electromagnetic calorimeter （ECAL）. This method was applied to reconstruct the ECAL test beam data for the Alpha Magnetic Spectrometer-02 （AMS-02）. The results show that this method can achieve an angular resolution of 7.36±0.08°/√E＋0.28±0.02° in the determination of the photon＇s direction, which is much more precise than that obtained with the commonly-adopted Center of Gravity （COG） method （8.4±0.1°/E＋0.8±0.3°）. Furthermore, since it uses only the properties of electromagnetic showers, this new method could also be used for other type of fine grain sampling calorimeters.